Tendencies in natural selection of high level young swimmers - Timakova, T.; Klyuchnikova, M. V. (Biomechanics and Medicine in Swimming XI, 2010)
INTRODUCTION: High level results in modern sport require the great physical and psychical efforts from young athletes. Some specialists offer to conduct the early orientation for children with usual abilities and gifted young ones. This problem has difficulties not only in search of such criteria but also in some social and moral aspects. Aim of this study was to find out facts of change in young swimming leaders, and to discover the reasons of this replacement. METHODS: We compared the data of two investigated young swimmers contingents, which optimal age for the best achievements came on the 1990s and on the first decade of 2000s. In total 210 girls and 216 boys aged 12-19 years were surveyed. We investigated testing data: 1) anthropometry and definition of biological age; 2) bio-energetic parameters and functional abilities of swimmers in swimming flume. Biological age (BA) defined by a method of the author (T.S.Timakova, 1986, 2006). Differs between chronologic age (CA) and BA distributed all swimmers over five groups: (R1, R2, N, À1; À2). The investigative data were processed by means of standard statistic methods. The classification and factor-typological description of objects were used as well. RESULTS: Comparison of 1990s swimmers contingent by the types of biological development showed the definite tendencies of age allocation. But only some athletes of younger ages moved forwards in the following years. Particularly it relates to the contingent of girls. At the 2000s swimming generation the shift towards increase of candidates age for national team selection was shown. The most of 15-16 years swimmers differed by signs of their age norm development. But at the next ages the number of retarded swimmers was increased in both sexes. In order to determine the reasons of young leaders change with the years we used 14-aged athletes classification in all volume of testing data. The different states of swimmers singled out classis were obtained. Two main reasons explain the character of leading swimmers change at different age groups. One cause is in shortterm advantage in ontogenesis for a part of swimmers. The other reason pertains to using of premature intensive training program for swimmers with more complicated variants of age development. CONCLUSION: The need of studying characters of age development in young swimmers was revealed. It allows to find the peculiarities in training process and to define the optimum age of the best achievements demonstration.